Pendampingan Verifikasi DPT Online melalui Media Brosur - Melati Budi Srikandi; William Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Elections are short for General Elections, which are a democratic process where citizens vote for their leaders and representatives through a voting process. Often, community participation as voters is still suboptimal and needs to be optimized. In the 2024 elections, it is necessary to conduct online voter list verification socialization in villages because rural residents often lack understanding of technology, where access to information technology in Indonesia still experiences gaps. Therefore, to increase voter participation, one effort that can be made is by creating a program